2004
DOI: 10.1385/mo:21:3:223
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine Monotherapy in Patients with Anthracycline- and Taxane-Pretreated Metastatic Breast Cancer

Abstract: The selection of chemotherapeutic regimens is challenging for metastatic breast cancer (MBC) patients whose diseases have failed to respond to anthracyline and taxane. Capecitabine has advantages of oral administration and favorable toxicity profiles. This study was conducted to evaluate the efficacy of capecitabine and to identify the subgroup of patients who would potentially have benefit from capecitabine monotherapy in patients with anthracycline- and taxane-pretreated MBC. Female patients with MBC who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Moreover, capecitabine alone emerged as an alternative to paclitaxel [25] or CMF [7] in patients for whom anthracycline-based combinations may not be appropriate, such as frail or elderly patients, patients with considerable comorbidities, or patient preference for oral chemotherapy. Other studies have shown that capecitabine monotherapy is effective in patients with metastatic breast cancer failing previous anthracycline- and taxane-based regimens [3,4,5,6]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, capecitabine alone emerged as an alternative to paclitaxel [25] or CMF [7] in patients for whom anthracycline-based combinations may not be appropriate, such as frail or elderly patients, patients with considerable comorbidities, or patient preference for oral chemotherapy. Other studies have shown that capecitabine monotherapy is effective in patients with metastatic breast cancer failing previous anthracycline- and taxane-based regimens [3,4,5,6]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, capecitabine is converted into fluorouracil by thymidine phosphorylase and therefore has the advantage of preferentially generating fluorouracil in the tumor tissue where thymidine phosphorylase is at a higher concentration [2]. The antitumor activity of single-agent capecitabine in metastatic breast cancer has been reported more frequently in anthracycline- and taxane-pretreated patients [3,4,5,6] than as first-line chemotherapy [7]. Treatment with capecitabine monotherapy allowed 15–29% of patients with metastatic breast cancer to achieve a clinical response despite treatment failure with taxane- and/or anthracycline-based therapy [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase II RCT by Talbot et al [42] compared the safety profile of single-agent capecitabine with that of singleagent paclitaxel in patients who had failed or were resistant to anthracycline-based therapy and/or who had undergone 19 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) All regimens used twice daily dosing, 2 weeks on/1 week off, unless otherwise noted.…”
Section: Safetymentioning
confidence: 99%
“…Lee et al [24] www.TheOncologist.com prior 5-FU therapy. The overall incidence of grade 3 AEs was lower but not statistically significant for those treated with single-agent capecitabine than for those treated with single-agent paclitaxel (36% vs. 68%; p = .06).…”
Section: Safetymentioning
confidence: 99%